Karakteristik dan Variabilitas Sifat-Sifat Fisik Tanah dan Evaluasi Kualitas Fisik Tanah pada Lahan Suboptimal - Rachman, Latief Mahir (Seminar Nasional Lahan Suboptimal, 2019)
Rachman, LM. 2019. Characteristic and variability of soil physical properties and evaluation of soil physical evaluation in suboptimal land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. Pp. 132-139. Palembang: Unsri Press.Â Self-reliance of food depends on how to optimizing dry land farming, especially enhancing productivity of soils in suboptimal lands. It needs strong direction and recommendation of soil management. Nowadays, soils on suboptimal lands encountered soil chemical, biological and physical problems to support optimal plant growth and production. Problems that are often arising are soil acidity, low availability of soil nutrients, low carbon organic content and low soil ability to serve available water for plant. The excellence fertilization technology is believed to be able to overcome the chemical aspects problems such as low of soil pH, soil nutrients and carbon organic content. However, problems related to soil physical properties are more difficult to be solved and need a longer period process for recovering, amendment and improvement. Correspondingly, a deep research needs to study the characteristics and variability of soil physical properties and soil physical quality of suboptimal lands. The purpose of study was to assess the characteristics and variability of soil physical properties and to evaluate soil physical quality on suboptimal lands. Soil physical properties that affecting soil physical quality analyzed is directed to aspects related to root development in soil, available water supply, and soil aeration, particularly soil depth, drainage, texture, bulk density or soil compaction, porosity, and soil pore distribution that controls the ability of soil to hold water, supply available water, release water and pull water very strong. Results of study conducted in 60 locations of suboptimal land, spread in 3 regencies and 2 cities in Banten Province and 6 regencies in West Java Province, showed that majority of their soil physical quality belong to moderate class. In fact, almost all of the soil physical properties that were studied did not show severe handicap for plant growth and production.Keywords: soil physical evaluation, soil physical properties, soil quality evaluation, suboptimal land